Prinsip Knowledge Integration dalam Pembelajaran Kimia di Sekolah Berdasarkan Pandangan Jabir Ibn Hayyan - Fitri Yati Sa’diah; Irawan; Aan Hasanah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This article discusses the integration of knowledge by Jabir Ibn Hayyan in teaching chemistry at schools based on Islamic perspectives. Its background includes the importance of integrating science and Islamic values in education. The research aims to explore whether knowledge has been integrated with other sciences in teaching chemistry at madrasah schools based on the perspective of integrating Jabir Ibn Hayyan's chemical knowledge. The method used is descriptive qualitative using questionnaires distributed to three chemistry teachers at madrasah schools. The research findings indicate that the integration of chemical knowledge based on Jabir Ibn Hayyan's principles is not uniformly used in teaching at madrasah schools. The conclusion of this study is that the understanding and application of Jabir Ibn Hayyan's knowledge integration principles in the context of teaching chemistry vary among chemistry teachers. The research's contribution highlights the need for further efforts to integrate Jabir Ibn Hayyan's concepts into the chemistry curriculum at madrasah schools to create a balanced learning environment between intellectual and spiritual aspects.